1992
DOI: 10.1088/0953-4075/25/20/008
|View full text |Cite
|
Sign up to set email alerts
|

Precise energy values of X-ray spin doublet levels

Abstract: The energy values of the individual members of those spin doublets of levels for certain atomic number ranges, for which only the experimentally obtained weighted averages of these energies were tabulated by Bearden and Burr (1967), have been calculated by using the screening parameters sigma 1 and sigma 2 previously reported by the authors. The energy values so obtained are further refined by the method of the modified Moseley plot. These refined energy values of the individual members of the spin doublets ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The Kβ 1,3 spin doublet values observed and calculated in this work are presented in Table IV and Fig. 6, together with other observed values [4,5,10] and the recommended values based on the experimental results of Campbell and Papp [42], the values obtained from a refinement of the modified Moseley plot method by Misra et al [43], and Pham et al [15]. The Lorentzian model was used for an analytic representation of Kβ x-ray lines [4,14], and the results of the fitting analyses are shown in Fig.…”
Section: A the Observed Kβ 13 Emission Spectrasupporting
confidence: 69%
“…The Kβ 1,3 spin doublet values observed and calculated in this work are presented in Table IV and Fig. 6, together with other observed values [4,5,10] and the recommended values based on the experimental results of Campbell and Papp [42], the values obtained from a refinement of the modified Moseley plot method by Misra et al [43], and Pham et al [15]. The Lorentzian model was used for an analytic representation of Kβ x-ray lines [4,14], and the results of the fitting analyses are shown in Fig.…”
Section: A the Observed Kβ 13 Emission Spectrasupporting
confidence: 69%
“…1d), then it is found that the points lying on the limbs of the unsymmetrical parabola do not now transform into a straight line parallel to the Z-axis. Instead, a plot comprising two inclined straight lines is generally obtained [6] with the vertex of the modified Moseley plot transforming into a point R which lies on the line joining the points of discontinuity P and Q of the above mentioned two inclined straight lines (Fig. 1d).…”
Section: Introductionmentioning
confidence: 99%